KALIBRASI PARAMETER HIDROLOGI DAERAH ALIRAN SUNGAI BENTUK RADIAL DENGAN APLIKASI HEC-HMS - Nanang Saiful Rizal; Hilfi Harisan Ahmad; Khairul Iqbal; Noor Salim (Universitas Muhammadiyah Jember, 2021)
One of the hydrological responses in a watershed is influenced by the shape of the watershed (DAS). Lempake watershed with an area of 194.50 km2 has a radial shape. So it is necessary to develop a model to determine the factors that influence the watershed with Radial Shapes using HEC HMS. The modeling that has been obtained at once can be used to calculate the inflow that enters the Lempake Dam, especially when there is significant rainfall. This study aims to obtain the value or magnitude of the parameters in the watershed with a radial shape, then the parameters obtained can be used to estimate the design flood discharge in a watershed with a radial shape. The research stage is to calculate the planned flood discharge from rain data from 2010 to 2019 with HEC HMS and then calibrate it with the flood discharge from field observations. from 2010 to 2019. Based on the results of the analysis, it was obtained that the planned flood discharge entering the Lemapke dam was m3/s and from the modeling results, the parameters of the radial type watershed were obtained, namely the CN value of 95 and the Initial Abstraction (Ia) value of 0.11 . This result has a correlation coefficient of 75%. with a relative error rate of 30%.